Osteocalcin Is Not Associated with the Risk of Type 2 Diabetes: Findings from the EPIC-NL Study - Zwakenberg, Sabine R. (PLoS One, 2015)
OBJECTIVE: To investigate whether total osteocalcin (tOC), uncarboxylated osteocalcin (ucOC) and percentage of uncarboxylated osteocalcin (%ucOC) are associated with the risk of type 2 diabetes. METHODS: This nested case control study included 1,635 participants, 833 incident diabetes cases and 802 non-diabetic control participants, aged 21–70 years from the EPIC-NL cohort. Baseline concentrations of tOC, ucOC and %ucOC were assessed. During 10 years of follow-up, diabetes cases were self-reported and verified against information from general practitioners or pharmacists. The association between the different forms of osteocalcin and diabetes risk was assessed with logistic regression adjusted for diabetes risk factors (waist circumference, age, sex, cohort, smoking status, family history of diabetes, hypertension, alcohol intake, physical activity and education) and dietary factors (total energy intake and energy adjusted intake of fat, fiber, protein and calcium). RESULTS: TOC concentration was not associated with diabetes risk, with an odds ratio (OR) of 0.97 (0.91–1.03) for each ng/ml increment after adjustment for diabetes risk factors and dietary factors. No association between ucOC and %ucOC and the risk of diabetes was observed either. In sex stratified analyses (P interaction = 0.07), higher %ucOC tended to be associated with an increased risk of type 2 diabetes in a multivariable model in women (OR 1.05 for each increment of 5% ucOC (1.00–1.11), P(trend) = 0.08), but not in men (OR 0.96 for each increment of 5% ucOC (0.88–1.04)). When waist circumference was replaced by body mass index, none of the osteocalcin forms were associated with the risk of type 2 diabetes in the final model among both women and men. CONCLUSIONS: Available evidence suggests that tOC, ucOC and %ucOC are each not associated with the risk of type 2 diabetes. However, more large-scale cohort studies are needed to clarify the presence of any association between the different forms of osteocalcin and the risk of type 2 diabetes.